Factors Determining the Risk Level of Chronic Obstructive Lung Disease (COPD) in Smokers in Bandung City: A Secondary Data Analysis - Agatha, Veronica; Sitanggang, Hendra Dhermawan; Wisudariani, Evy; Hubaybah, Hubaybah; Fitri, Adelina; Gultom, Mauliate DC (RRZ Scientific Publishing, 2024)
Chronic obstructive pulmonary disease (COPD) is a major contributor to illness and death. COPD can result in the obstruction of airflow and disturbance of the respiratory system. These symptoms have a tendency to be enduring and progressively worse. In Indonesia, the number of persons affected by COPD is estimated to be 9.2 million, with smokers being the primary cause of COPD cases. Hence, the objective of this study was to determine the risk variables linked to the occurrence of COPD among smokers in Bandung City in 2022. This study employed a cross-sectional design, with a sample size of 189 smokers aged over 40 years in Bandung City. The participants were selected via total sampling. This study employed secondary research methodology, utilising chi-square and binary regression analysis for data analysis. The findings indicated that the prevalence of high-risk COPD cases in Bandung City in 2022 was 12.7%. An relationship was seen between age, smoking intensity, namely 20-30 packs of cigarettes per year, and level of physical activity. After controlling for age, physical activity, and degree of smoking, the primary cause of the increased risk of COPD was the consumption of 20-30 packs of cigarettes per year (PR= 11.34; 95% CI = 1.65 to 77.67). This study highlights the significance of lifestyle interventions, such as smoking cessation programmes and CERDIK's behaviours, in managing COPD.